2017
DOI: 10.1159/000479119
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Discoidin Domain Receptor 1 in Inflammation, Fibrosis and Renal Disease

Abstract: Discoidin domain receptors (DDRs) are a family of 2 non-integrin collagen receptors, DDR1 and DDR2, which display a tyrosine kinase activity. They are mainly expressed during embryonic development and their role during adulthood is very limited. DDR1 has been widely studied in several types of cancers, in atherosclerosis and fibrosis, but also in chronic kidney disease (CKD). This review focuses on the role of DDR1 in chronic nephropathies and on the effect of its deletion in the pathological processes involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 49 publications
3
32
0
Order By: Relevance
“…Another strategy to perturb DDR1 function is the use of inhibitors of receptor tyrosine kinases such as imatinib or nilotinib. Both have given mixed results so far, most likely due to their lack of selectivity and secondary effects [152]. In vitro studies showed that nilotinib reduces the association of DDR1 with myosin IIA and blocks collagen contraction [13].…”
Section: Targeting Ddr1 In Anti-fibrotic Therapiesmentioning
confidence: 99%
“…Another strategy to perturb DDR1 function is the use of inhibitors of receptor tyrosine kinases such as imatinib or nilotinib. Both have given mixed results so far, most likely due to their lack of selectivity and secondary effects [152]. In vitro studies showed that nilotinib reduces the association of DDR1 with myosin IIA and blocks collagen contraction [13].…”
Section: Targeting Ddr1 In Anti-fibrotic Therapiesmentioning
confidence: 99%
“…7 DDR1 expression is upregulated in fibrosed organs including the kidney and it contributes to disease progression by regulating inflammatory and fibrotic responses. 13 We showed that DDR1 promotes collagen IV production, a major ECM upregulated in fibrotic diseases. This effect requires collagen binding to DDR1 and receptor kinase domain activation; however, the molecular mechanisms whereby DDR1 increases ECM synthesis and contributes to fibrosis initiation and/or progression is poorly defined.…”
mentioning
confidence: 91%
“…Discoidin Domain Receptor 1 (DDR1) is a cell-surface tyrosine kinase receptor that binds to, and is activated by, collagens [16][17][18][19] . DDR1 is predominantly expressed in normal epithelial cells and its aberrant expression is associated with multiple solid cancer types.…”
Section: Introductionmentioning
confidence: 99%
“…Under various physiopathological conditions such as hypertensive nephropathy, collagen-triggered DDR1 activation is known to induce an inflammatory response, which in turn leads to excessive collagen synthesis and exaggerated fibrosis 19 (Figure 2c). Expression of Col3a1 and a-smooth muscle actin (a-SMA), another hallmark for accumulation of tumor-associated stromal cells 32 , followed the same trend, albeit not statistically significant (Figure 2c).…”
mentioning
confidence: 99%
See 1 more Smart Citation